Pengaruh Kompetensi, Teknologi Informasi, Persepsi Resiko Dan Tingkat Literasi Keuangan Terhadap Minat Investasi Crypto Currency - Noel Multi Kristian Ujung; Riadi Riadi; Jenisa Satya; Desy Astrid Anindya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research started from the development of crypo investment so that it has become a cornerstone in this study is to analyze the influence of competence, Information Technology, Risk Perception and level of financial literacy on crypto currency investment interests. To complete this study there are 98 respondents and use simple random sampling. The conclusion of this study is that simultaneously and partially competence, information technology, risk perception and level of financial literacy have a positive and significant effect on crypto currency investment interested. Keywords: Competence, Information Technology, Risk Perception, Financial Literacy Level, Investment Interest.